Analisis Psikologis Karakter Kaluna dalam Film “Home Sweet Loan”: Prspektif Id, Ego, Superego - Nasution, Aisyah Rizkiah; Apriani, Nur Sakinah; Syafrina Ulfa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study analyzes the character of Kaluna in the film Home Sweet Loan using Sigmund Freud's psychoanalytic theory, which divides personality structure into three main components: id, ego, and superego. This study aims to understand the psychological dynamics of Kaluna in facing inner conflicts between personal desires and social demands. This study found that Kaluna experiences tension between her instinctive desire (id) to have her own home, her realistic ability (ego) in managing finances, and her moral values ​​(superego) that require her to remain responsible for her family. This study uses a descriptive qualitative approach to analyze the psychological dynamics of Kaluna's character in the film Home Sweet Loan. The type of research used is a literature study with a focus on film analysis as the object of study. The main data source is the film Home Sweet Loan, while the secondary data includes books, articles, journals, and other sources relevant to Sigmund Freud's psychoanalytic theory and character studies in the film. Data collection techniques are carried out through observation of scenes in the film, recording dialogues, and identifying Kaluna's actions and reactions that reflect aspects of the id, ego, and superego. The data analysis technique used is content analysis with reference to Freud's psychoanalytic theory, which aims to reveal the interaction between the psychic components in Kaluna when facing conflict and decision making throughout the storyline. This study contributes to understanding the psychological impact of economic dilemmas on individuals in the sandwich generation, especially for women who are at the crossroads between personal aspirations and family loyalty.